2008
DOI: 10.1086/587544
|View full text |Cite
|
Sign up to set email alerts
|

Dissipation and Extra Light in Galactic Nuclei. I. Gas‐Rich Merger Remnants

Abstract: We study the origin and properties of "extra" or "excess" central light in the surface brightness profiles of remnants of gas-rich mergers. By combining a large set of hydrodynamical simulations with data on observed mergers that span a broad range of profiles at various masses and degrees of relaxation, we show how to robustly separate the physically meaningful extra light -i.e. the stellar population formed in a compact central starburst during a gas-rich merger -from the outer profile established by violent… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
175
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 158 publications
(191 citation statements)
references
References 125 publications
16
175
0
Order By: Relevance
“…and studied 2MASS and kinematic data of NGC 3718, for which they find elliptical-like 18 We agree with Hopkins et al (2008) on the danger of doing three component fits. Our fit is indeed very sensitive to the adopted lower and upper limits.…”
Section: To Bulge or Not To Bulge?supporting
confidence: 53%
See 2 more Smart Citations
“…and studied 2MASS and kinematic data of NGC 3718, for which they find elliptical-like 18 We agree with Hopkins et al (2008) on the danger of doing three component fits. Our fit is indeed very sensitive to the adopted lower and upper limits.…”
Section: To Bulge or Not To Bulge?supporting
confidence: 53%
“…Kormendy & Ho (2013), Hopkins et al (2008Hopkins et al ( , 2009a, instead of the observed core. The suggested absence of sufficient amounts of nuclear gas, however, lead naturally to the limited star formation observed.…”
Section: Putting the Pieces Togethermentioning
confidence: 78%
See 1 more Smart Citation
“…In particular, the low value of n unveil the kind of mergers that have formed the galaxy. In order to get a similar light profile it is required a very gas rich merger for the progenitors (∼80% gas rich; see Hopkins et al 2008). Figure 10 shows the velocity distribution of the 78 member galaxies.…”
Section: Photometric Properties Of the Brightest Group Galaxymentioning
confidence: 99%
“…Moreover, burst of star formation driven by the interaction (see e.g. Naab et al, 2006, Hopkins et al, 2008 and references therein) could continously seed new magnetic field, thus intensifying the amplification of magnetic fields even more.…”
Section: Introductionmentioning
confidence: 99%